ECONOMIC EFFECTS OF COVID-19 ON WORLD AND TURKISH CIVIL AVIATION INDUSTRY - MERİÇ, Serkan (Atlas Journal, 2021)
Many precautions are taken to prevent the spread of the Covid-19 virus, which emerged in China and affected the whole world. However, the pandemic continues to negatively affect the aviation industry, as it does every other sector. In this study, the data related to aviation sector of both worldwide and Turkey both pre-pandemic and after pandemic were examined. It has been tried to make predictions for the upcoming periods by comparing the data of both periods. Considering that the effects of the pandemic process, which caused great economic damage to the global aviation industry, will continue, the study is expected to contribute to both the literature and aviation businesses.